Supercapacitors based on patronite–reduced graphene oxide hybrids: experimental and theoretical insights1. Issue 37 (7th October 2015) - Ratha, Satyajit; Marri, Subba R.; Lanzillo, Nicholas A.; Moshkalev, Stanislav; Nayak, Saroj K.; Behera, J. N.; Rout, Chandra Sekhar
<x xml:space="preserve">Abstract</x> Experimental and theoretical investigations of VS4/RGO hybrids towards their possible application as supercapacitors for energy storage.